PENERAPAN DIGITAL MARKETING BAGI UMKM KULINER DI TAMAN KOTA MAS DAN SIMPANG KARA BATAM - Wisnu Yuwono; Johny Budiman; Desmond Lim; Cindy Fransiska; Felicia Koo; Jessica Jessica; Jessy Valencia; Lydia Sasmita; Novita Novita; Wilfi Caroline (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Pandemic Covid-19 changed many community activities in the world, one of them is our country Indonesia. Starting from working, studying, to shopping online from home. That makes the use of the internet every day has increased. This pandemic COVID-19 can be an opportunity for business entrepreneurs to survive in this situation. By taking advantage of technology and moving from offline to online marketing trends. This progress is considered very useful to be used as a business marketing strategy, namely digital marketing. The purpose of this community service is to equip Culinar SMEs in Taman Kota Mas and Simpang Kara Batam in mastering and utilizing digital marketing through social media. The method used is directly going to partner, developed, and trained partner with Instagram, Facebook, WhatsApp, listed partner to Gofood, and Grab food for business partners. The results program last for one semester showed that digital marketing is a very important role and take effect especially in this pandemic COVID-19 situation very helpful in increasing sales and expanding the market share of culinary SMEs in Taman Kota Mas and Simpang Kara Batam.